Islamic NGOs under Different Authoritarian Regimes - Aly, Rana (AUC Knowledge Fountain, 2021)
The state-civil society relationship has always been a highly controversial sphere specially when it comes to the Middle East. The exceptional complexities of the region make the dynamics of this relationship more questionable. The case of Egypt is a salient manifestation of these complexities where NGOs used to function under some variants of authoritarianism. Precisely, Islamic charities used to be one of the main social services providers for many decades in Egypt and which were tolerated to a great extent by the previous regimes in order to compensate for the lack of the services provided by the regime. Having these Islamic organizations as a parallel services provider for long time led to the emergence of a hyper-rational approach which assumed that these organizations will be permanently tolerated by the regime as long as it is economically unable to satisfy the needs of the public. However, post-2013 empirics showed that this approach is no longer valid due to the crackdown on many Islamic NGOs in addition to other drastic measures that aimed at containing their potential threat. In order to test the validity of this approach, a comparison between Mubarak’s regime and Sisi’s regime was conducted to measure the impact of economic hardships and the threat to the regime on one hand on the autonomy of Islamic NGOs on the other. The result showed that the higher the threat to authoritarian rule, the lower the autonomy of these organizations irrespective of the deteriorating economic conditions. On this basis, I provide throughout this study a detailed process of revisiting the aforementioned approach in addition to offering a new approach that is more capable of explaining the recent variations/circumstances.